Penerapan Aqidah Akhlak dalam Pendidikan Homeschooling: Mengajarkan Sifat-sifat Allah dan Akhlak Terpuji dalam Kehidupan Sehari-hari - Ahmad Rudi Alpata (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
The education of Aqidah Akhlak plays a crucial role in shaping a child's character and personality. One effective method to instill Aqidah Akhlak is through homeschooling. Homeschooling offers the opportunity for more personalized and in-depth education, allowing for a better understanding of the core concepts of Aqidah Akhlak. This article aims to discuss the application of Aqidah Akhlak in homeschooling education, specifically focusing on teaching the essential attributes of Allah and magnifying His greatness, as well as instilling virtuous character traits such as honesty and respect for parents. Additionally, the article will explore effective strategies for implementing Aqidah Akhlak in daily life. Homeschooling provides an ideal environment to strengthen spiritual growth and character development, offering flexibility to integrate Islamic teachings into daily activities. By using role modeling, interactive learning, and real-life application, parents can guide their children to understand the divine attributes of Allah while nurturing moral values. This holistic approach ensures that children not only learn about their faith but also apply it in their actions and interactions with others. Aqidah Akhlak serves as a crucial foundation in shaping a faithful and virtuous character. By understanding Aqidah, children can better appreciate the moral values taught in Islam, such as honesty, compassion, and peace.